Modeling and Simulation of Silicon Solar Cell in MATLAB/SIMULINK for Optimization - Ehsan Hosseini (Institute of Advanced Engineering and Science, 2014)
One of the most significant current discussions in life is solar energy and has been in use since the beginning of time. Increasingly, man is learning how to yoke this important resource and use it to replace traditional energy sources. Recent developments in the field of solar energy have led to a renewed interest in Solar cells to store this energy and reproduce electricity. Unfortunately the amount of energy converted is very less, that is the efficiency of conversion is poor. The major problem is to improve the efficiency so that the losses can be minimized. In this project the Maximum Power Points are found and the Fill Factor is calculated. In this paper using MATLAB and SIMULINK model the comparison of silicon solar cell and type of panels is done.